Apharinodes baixiensis sp. nov., a new species from Guangdong, China (Coleoptera, Staphylinidae, Pselaphinae) - Jiang Zhu; Cheng-Bin Wang (Biodiversity Data Journal)
The genus Apharinodes Raffray, 1890 (Coleoptera, Staphylinidae, Pselaphinae, Hybocephalini) includes four known species occurring in East and Southeast Asia.A new species, Apharinodes baixiensis sp. nov., is described from Heyuan City, Guangdong Province, China. Important morphological characters of the new species are illustrated by colour plates.